Regional diagnostic petrophysical features of the Antarctic peninsula breeds (near the station «Akademik Vernadsky») - Korchin, V. A.; Burtny, P. A.; Karnaukhova, E. E.; Nech, A. S. (Ukrainian Antarctic Journal, 2010)
At atmospheric pressure and room temperature, at maximal axleloadings, and also at high hydrostatical pressure resiliently-closeness descriptions are studied more than 200 standards of different breeds in the district of the station «Akademik Vernadsky» (Ukraine). Their resilient anisotropy is investigational. It is set that the last is conditioned the oriented location of defects of mineral environment, and in less degree related to the orientation of rock-forming minerals. The models of distributing of mineral matter are built with a depth along the seismic types of DSS 10, 12, 13 near-by the station «Akademik Vernadsky».